The Impact of Borrowing Debt on the Efficiency Loss of Municipal Infrastructure Investment and Construction - Xiaojie Li; Hao Li; Fei Qiu (Discrete Dynamics in Nature and Society)
Borrowing debt has impacted on the financing effect and governance effect of investment entities. Borrowing debt has become an important financing channel for the investment and construction of municipal infrastructure in China. In this paper, panel data from 2003 to 2018 in cities above the prefecture level in China are used to study the impact of borrowing debt on the efficiency loss of municipal infrastructure investment and construction. First, the results indicate that financing constraints have a greater impact than agency costs for the investment and construction of municipal infrastructure in China. Second, borrowing debt can effectively reduce the efficiency loss of municipal infrastructure investment and construction due to financing constraints. Third, the governance effect of borrowing debt is not very positive, but the rigid repayment of debt and interest to international banks will play some positive governance effects in the later stage.